Design of a Web-Based Bus Rental Information System for PO Dika Trans - Mahendra, Farhan Ihza; Sudarmilah, Endah (Journal La Multiapp, 2025)
Information technology is developing rapidly and has an impact on almost every area of life, one of these information media is the Internet. The progress of the times has had an indirect impact on the world of transactions, namely changing the transaction system from conventional to online, therefore there are several business opportunities that are exploited by individuals or companies in Indonesia. PO Dika Trans is a domestic company domiciled in Klaten Regency, operating in the transportation sector. This research aims to design and implement a web-based information system at PO Dika Trans. The use of technology is expected to provide convenience in all aspects and provide expansion of the company's promotional network at relatively low costs. This research uses the System Development Life Cycle (SDLC) waterfall model method. The waterfall model was chosen because it has structured and sequential stages. Testing uses the blackbox method and usability scale system. The system's expected results can be realized and easily accessed by users.